An introduction to Stata programming - Baum, Christopher F. (College Station, Texas : StataCorp LP, 2016)
'The second edition of this book contains several new recipes illustrating how do-files, ado-files, and Mata functions can be used to solve programming problems. Several recipes have also been updated to reflect new features in Stata added between versions 10 and 14. The discussion of maximum-likelihood function evaluators has been significantly expanded in this edition. The new topics covered in this edition include factor variables and operatores; use of margins, marginsplot, and suest; Mata-based likelihood function evaluators; and associative arrays.'--Preface.
Includes bibliographical references (pages 397-402) and indexes.
Keywords: Social sciences -- Statistical methods -- Computer programs; Statistics -- Computer programs -- Handbooks, manuals, etc